Invitation coverage and participation in Italian cervical, breast and colorectal cancer screening programmes. (March 2018) - Giorgi Rossi, Paolo; Carrozzi, Giuliano; Federici, Antonio; Mancuso, Pamela; Sampaolo, Letizia; Zappa, Marco
Objectives: In Italy, regional governments organize cervical, breast and colorectal cancer screening programmes, but there are difficulties in regularly inviting all the target populations and participation remains low. We analysed the determinants associated with invitation coverage of and participation in these programmes. Methods: We used data on screening programmes from annual Ministry of Health surveys, 1999–2012 for cervical, 1999–2011 for breast and 2005–2011 for colorectal cancer. For recent years, we linked these data to the results of the national routine survey on preventive behaviours to evaluate the effect of spontaneous screening at Province level. Invitation and participation relative risk were calculated using Generalized Linear Models. Results: There is a strong decreasing trend in invitation coverage and participation in screening programmes from North to South Italy. In metropolitan areas, both invitation coverage (rate ratio 0.35–0.96) and participation (rate ratio 0.63–0.88) are lower. An inverse association exists between spontaneous screening and both screening invitation coverage (1–3% decrease in invitation coverage per 1% spontaneous coverage increase) and participation (2% decrease in participation per 1% spontaneous coverage increase) for the three programmes. High recall rate has a negative effect on invitation coverage in the next round for breast cancer (1% decrease in invitation per 1% recall increase). Conclusions: Organizational and cultural changes are needed to better implement cancer screening in southern Italy.